PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU PADA RESTORAN BBCO DI HOTEL JW MARRIOTT BANGKOK - Apitha Zahra Esha Saviera; I Ketut Sutapa; Desak Made Purnama Dewi (Universitas Triatma Mulya, 2023)
The purpose of this study was to determine guest satisfaction at the BBCO restaurant at the JW Marriott Bangkok Hotel. The independent variables used are product quality and service quality. This study uses a questionnaire method in obtaining related data and information for analysis. The data used in this study are primary data obtained from the results of filling out questionnaires by having used the BBCO Restaurant product at the JW Marriott Bangkok Hotel, totaling 85 guests. Sampling in this study used a purposive sampling technique with a sampling technique through the number of indicators multiplied by a margin of error of 5%. The number of samples in this study were 85 respondents. The data analysis method used is the classical assumption test, multiple linear regression analysis. This study uses the t-test to determine the significance of the effect of the product quality and service quality variables on the guest satisfaction variable partially and the F-test to test the simultaneous effect of all independent variables on the dependent variable. The results of this study indicate that the independent variables, namely product quality and service quality, have a positive and significant effect on guest satisfaction at the BBCO Restaurant at the JW Marriott Hotel Bangkok. The results of the coefficient of determination show that the influence of product quality and service quality on guest satisfaction has an influence percentage of 40.6%.